2003
DOI: 10.1002/pca.689
|View full text |Cite
|
Sign up to set email alerts
|

On‐line identification of unstable catalpol derivatives from Jamesbrittenia fodina by LC‐MS and LC‐NMR

Abstract: LC-UV-MS analysis of the methanol extract of Jamesbrittenia fodina O. M. Hilliard (Scrophulariaceae) revealed the presence of cinnamic ester derivatives. Two isomeric pairs of these constituents were detected, but could not be isolated. In order to identify these unstable compounds, LC-1H-NMR spectra were obtained for each individual isomer and standard NMR measurements were performed in-mixture. The spectra clearly demonstrated that the fractions consisted of mixtures of cis and trans cinnamoyl catalpol glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…The same signals were observed in the proton NMR analysis of each fraction, but with slightly different chemical shifts, which suggests that a possible mixing of the compounds may take place, like a mixture previously analyzed by Cogne et al [14]. It can also be observed that two different proton signals are observed for the p-coumaroyl moiety, corresponding to the two different isomers, as follows: H5/H9 (Z) (δ 7.71), and H5/H9 (E), (δ 7.48) respectively; H6/H8 (Z)/(E), (δ 6.81 and 6.77) ( Figure 5).…”
Section: Resultssupporting
confidence: 73%
“…The same signals were observed in the proton NMR analysis of each fraction, but with slightly different chemical shifts, which suggests that a possible mixing of the compounds may take place, like a mixture previously analyzed by Cogne et al [14]. It can also be observed that two different proton signals are observed for the p-coumaroyl moiety, corresponding to the two different isomers, as follows: H5/H9 (Z) (δ 7.71), and H5/H9 (E), (δ 7.48) respectively; H6/H8 (Z)/(E), (δ 6.81 and 6.77) ( Figure 5).…”
Section: Resultssupporting
confidence: 73%
“…7) were analysed in the same way in the extract. 24 In the same extract, another cinnamic ester derivative 34a revealed a different type of instability. Indeed, 34a was found to be transformed after isolation and lyophilisation into two additional compounds 34a1 and 34a2 sharing the same UV and same molecular weight as their parent molecule 34a (Fig.…”
Section: Study Of Unstable Natural Products By On-flow and Stop-flow mentioning
confidence: 97%
“…24 A preliminary metabolite profiling study performed with LC/UV-DAD and LC/ESI-MS revealed the presence of various common cinnamic ester derivatives. On the basis of this first chemical screening results, the attention was focused on a pair of putative new isomeric compounds 32a/32b.…”
Section: Study Of Unstable Natural Products By On-flow and Stop-flow mentioning
confidence: 99%
“…The mass of the compounds and the mass of lost fragment indicated the presence of prenylated isoflavanones or isoflavones; LC-NMR and MS-MS finally confirmed that result. In the publications of Schaller et al (2001) and Cogne et al (2003), crude plant extracts were analyzed by LC/ thermospray-MS and LC-UV-ESI/MS to determine the presence of certain classes of compounds such as diterpenic compounds and unstable cinnamic ester derivatives, respectively, whereas NMR experiments established the structure of isomeric pairs. Generally, it was observed that MS detection was more sensitive than NMR to detect the metabolites, but was less efficient for compound identification.…”
Section: Lc-ms For Metabolite Profilingmentioning
confidence: 99%